2006
DOI: 10.1080/02522667.2006.10699686
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between service quality and customer satisfaction: the example of CJCU library

Abstract: The present paper, taking Chang Jung Christian University (CJCU) Library as an example, investigates the users' degree of importance and the performance provided by the library. This study explores overall user satisfaction as well. A questionnaire survey is conducted to reveal users' perspectives on service quality. Based on literature, service quality has five dimensions, which are tangibles, responsiveness, reliability, assurance, and empathy. The results indicate that the overall service quality has a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 12 publications
6
73
1
7
Order By: Relevance
“…An overall satisfaction question is often asked as part of the typical citizen survey and has been used as a key dependent variable of interest in research of service delivery (Ryzin, 2006). Previous studies proved that service quality had a positive relation with customer satisfaction (Wang & Shieh, 2006;Ismail, Ridzuan, Ranlan, Bin, Rahman, & Francis, 2013;Vu & Huan, 2016). Furthermore, service quality significantly influenced customer satisfaction.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…An overall satisfaction question is often asked as part of the typical citizen survey and has been used as a key dependent variable of interest in research of service delivery (Ryzin, 2006). Previous studies proved that service quality had a positive relation with customer satisfaction (Wang & Shieh, 2006;Ismail, Ridzuan, Ranlan, Bin, Rahman, & Francis, 2013;Vu & Huan, 2016). Furthermore, service quality significantly influenced customer satisfaction.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…For instance, Oliver [1993] and Auh and Johnson [2005], have viewed service quality and customer satisfaction as complementary or divergent constructs. Other researchers further established the causal reciprocity of service quality and customer satisfaction, which creates further confusion [Salazar, Paulo, 2004;Wang, Chich-Jen, 2006]. Similarly, the claim that customer satisfaction leads to loyalty appears even less convincing [Egan, 2004;Pritchard, Silvestro, 2005].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…(Dahiyat, Akroush, & Lail, 2011) claimed that the service quality is an important antecedent of customer satisfaction. (Wang & Shieh, 2006) found that except responsiveness, all the five dimensions of SERVQUAL explored have a significant positive effect on overall user satisfaction. Other research studies confirming the relationships between customer satisfaction and service quality dimensions depict mixed results.…”
Section: Service Quality and Customer Satisfactionmentioning
confidence: 90%